Sex Differences in Large Artery Stiffness: Implications for Cerebrovascular Dysfunction and Alzheimer’s Disease - Kehmeier, Mackenzie N.; Walker, Ashley E. (Frontiers in Aging, 2021)
Two in every three Alzheimer’s disease diagnoses are females, calling attention to the need to understand sexual dimorphisms with aging and neurodegenerative disease progression. Dysfunction and damage to the vasculature with aging are strongly linked to Alzheimer’s disease. With aging there is an increase in stiffness of the large elastic arteries, and this stiffening is associated with cerebrovascular dysfunction and cognitive impairment. However, it is unclear how the deleterious effects of arterial stiffness may differ between females and males. While environmental, chromosomal, and sex hormone factors influence aging, there is evidence that the deficiency of estrogen post-menopause in females is a contributor to vascular aging and Alzheimer’s disease progression. The purpose of this mini review is to describe the recent developments in our understanding of sex differences in large artery stiffness, cerebrovascular dysfunction, and cognitive impairment, and their intricate relations. Furthermore, we will focus on the impact of the loss of estrogen post-menopause as a potential driving factor for these outcomes. Overall, a better understanding of how sex differences influence aging physiology is crucial to the prevention and treatment of neurodegenerative diseases.